2016
DOI: 10.18632/oncotarget.13813
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of transcatheter arterial chemoembolization plus radiofrequency ablation versus transcatheter arterial chemoembolization alone for hepatocellular carcinoma

Abstract: This meta-analysis was conducted to compare transcatheter arterial chemoembolization (TACE) plus radiofrequency ablation (RFA) with TACE alone for hepatocellular carcinoma. We searched MEDLINE, EMBASE and CENTRAL for all relative randomized controlled trials (RCTs) and retrospective studies until October 31 2016. Tumor response, recurrence-free survival, overall survival and postoperative complications were the major evaluation indices. Review Manager (version 5.3) was used to analyze the data. Dichotomous dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…They analyzed six studies with 534 patients and showed similar OS and RFS. Yang et al [ 21 ] investigated the outcome of TACE+RFA compared to TACE alone in HCC patients. They showed a survival benefit for combined therapy compared to TACE alone (OR 1-year = 3.92, 95% CI = 2.41–6.39, p <0.00001; OR 3-year = 2.56; 95% CI = 1.81–3.60; p <0.00001; OR 5-year = 2.78, 95% CI= 1.77–4.38; p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…They analyzed six studies with 534 patients and showed similar OS and RFS. Yang et al [ 21 ] investigated the outcome of TACE+RFA compared to TACE alone in HCC patients. They showed a survival benefit for combined therapy compared to TACE alone (OR 1-year = 3.92, 95% CI = 2.41–6.39, p <0.00001; OR 3-year = 2.56; 95% CI = 1.81–3.60; p <0.00001; OR 5-year = 2.78, 95% CI= 1.77–4.38; p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…31 Despite the limited number of randomized studies, several meta-analyses have been published in the attempt to assess the value of combined TACE-RFA compared with monotherapies (►Table 2). [32][33][34][35][36][37][38][39] The majority of these meta-analyses confirmed that the combination therapy is able to significantly improve local tumor control and OS compared with either RFA or TACE, in selected populations. In particular, while there seems not to be any advantage in small and large-size tumors, the combined approach should be indicated for lesions 3 to 5 cm in size.…”
Section: Resultsmentioning
confidence: 66%
“…In comparison, the LTP rates after TACE-RFA have generally been lower than those of RFA alone, with previously published rates of 2.9%–14.5% over median follow-up periods of 37.0–50.0 months. [678910] Kim et al . [7] observed LTP in 40% of treated lesions in the combined treatment group and 70% in the RFA-alone group.…”
Section: Discussionmentioning
confidence: 99%
“…in their meta-analysis concluded that use of TACE plus RFA for intermediate stage hepatocellular carcinoma can attain higher tumor response rates and improve survival rates than TACE alone. [8] According to Xie et al ., the 1-, 2-, 3-, 4- and 5-year overall survival rates after RFA and TACE treatment were 97.5%, 89.4%, 84.2%, 80.4% and 78.7%, respectively. [14]…”
Section: Discussionmentioning
confidence: 99%